Films Based on Blends of Polyvinyl Alcohol and Microbial Hyaluronic Acid - Pan,Nicole Caldas (2020)
Abstract The aims of this work were to produce hyaluronic acid (HA) by Streptococcus zooepidemicus ATCC 39920 in a low cost sugarcane molasses fermentation medium and to employ the produced HA to obtain films blends based on polyvinyl alcohol (PVA). The films were produced using solution casting method and they were characterized according to their microstructure, mechanical and barrier properties. HA was added in different concentrations (0, 5, 10 and 15% (w/w)), and glycerol was used as a plasticizer (25 g/100 g solids). All formulations resulted in easily manipulated films with good appearance. The addition of HA on PVA films increased their thermal stability, solubility, swelling index, water vapor permeability and elongation. Microbial HA sample combined with PVA showed to be a promising material to biomedical application, and an addition between 5 and 10% (w/w) was sufficient to improve PVA films properties.